Ligaclip for Preauricular Skin Tags in the Newborn - Schonauer, Fabrizio; Guastafierro, Antonio; Grasso, Elisabetta; Izzo, Sara; Nicoletti, Giovanni Francesco; D'Andrea, Francesco (European Journal of Pediatric Surgery, 2020)
Introduction Skin tags are benign lesions, that often represent only an aesthetic problem; if subjected to trauma, they can occasionally bleed with possible infection and pain. When they occur in the preauricular region, attention should be paid to the diagnosis and approach; in fact, controversy exists in the differential diagnosis between hair follicle nevi, accessory tragus, and skin tag. Misdiagnosis and failure of treatment can lead to serious consequences, such as chondritis.Materials and Methods In our retrospective study, we evaluated 19 newborns affected by single, unilateral skin tag in the preauricular region. Each patient underwent a careful clinical examination; lesions without a pilosebaceous unit and with a thin, soft pedicle were treated in the nursery with Ligaclip (Johnson & Johnson).Results Skin tag falls between day 7 and 10. We had no cases of edema, cellulitis, clip loss, or bleeding. Scarring results were extremely satisfactory at 3-month follow-up.Conclusion We believe that after a careful clinical examination, cases of skin tags in the preauricular area can be selected and treated with Ligaclip. This procedure can be considered rapid, safe, economical, and simple in the newborn patients.
Keywords: skin tag; newborn; Ligaclip; preauricular